Funding deposit insurance - Dick Oosthuizen; Ryan Zalla (European Central Bank (ECB), 2022)
We present a quantitative model of deposit insurance. We characterize the policymaker's optimal choices of coverage for depositors and premiums raised from banks. Premiums contribute to a deposit insurance fund that lowers taxpayers' resolution cost of bank failures. We find that riskadjusted premiums reduce moral hazard, enabling the policymaker to increase deposit insurance coverage by 3 percentage points and decrease the share of expected annual bank failures from 0.66% to 0.16%. The model predicts a fund-to-covered-deposits ratio that matches the data and declines in taxpayers' income due to taxpayers' risk aversion.
Keywords: G21; G28; 330; Deposit Insurance; Bank Runs; Bank Regulation